Multiple endocrine neoplasia and hyperparathyroid-jaw tumor syndromes: clinical features, genetics, and surveillance recommendations in childhood - Wasserman, Jonathan; Tomlinson, Gail E.; Pajtler, Kristian Wilfried (Clinical cancer research, 2017)
Children and adolescents who present with neuroendocrine tumors are at extremely high likelihood of having an underlying germline predisposition for the multiple endocrine neoplasia (MEN) syndromes, including MEN1, MEN2A and MEN2B, MEN4, and hyperparathyroid-jaw tumor (HPT-JT) syndromes. Each of these autosomal dominant syndromes results from a specific germline mutation in unique genes: MEN1 is due to pathogenic MEN1 variants (11q13), MEN2A and MEN2B are due to pathogenic RET variants (10q11.21), MEN4 is due to pathogenic CDKN1B variants (12p13.1), and the HPT-JT syndrome is due to pathogenic CDC73 variants (1q25). Although each of these genetic syndromes share the presence of neuroendocrine tumors, each syndrome has a slightly different tumor spectrum with specific surveillance recommendations based upon tumor penetrance, including the age and location for which specific tumor types most commonly present. Although the recommended surveillance strategies for each syndrome contain similar approaches, important differences do exist among them. Therefore, it is important for caregivers of children and adolescents with these syndromes to become familiar with the unique diagnostic criteria for each syndrome, and also to be aware of the specific tumor screening and prophylactic surgery recommendations for each syndrome. Clin Cancer Res; 23(13); e123-e32. ©2017 AACR. - See all articles in the online-only CCR Pediatric Oncology Series.
Gesehen am 04.12.2018